Réponses

Meilleure réponse !
2014-04-03T18:41:39+02:00
Bonsoir

B= 9(x²+1)+3x+4)(-x+1)+3(4x-16)
B = 9x² + 9 + (-3x²+3x-4x +4) + 12x - 48
B = 9x² +9 -3x² +3x -4x +4 +12x -48
B = 6x² +11x -35

C= 8(x²-4)-(x+6)(2x-4)+(19x-27)
C = 8x²-32 - (2x² -4x +12x -24) + 19x -27
C = 8x² -32 -2x² +4x -12x +24 +19x -27
C = 6x² +11x -59

D= 3x(3x+4)-x(1+3x)-35
D = 9x² +12x - x -3x -35
D = 9x² +8x -35

Merciii !!
j'ai oublié un ² dans la D : 9x² +12x - x -3x² -35 = 6x² +11x -35. Mille excuses
Ce n'est pas grave :D
2014-04-03T18:44:07+02:00
Ps: x^2 = x au carre

B= 9x^2+9+(-3x^2+3x-4x+4)+12x-48
B= 9x^2+9-3x^2+3x-4x+4+12-48
B= 6x^2-x-23

C=8x^2-32-(2x^2-4x+12x-24)+19x-27
= 8x^2-32-2x^2+4x-12x+24+19x-27
=6x^2+17x-35

D= 9x^2+12x-x-3x^2-35
=6x^2+11x-35
s'il n'y a pas de faute de calcul, c'est ça